Kedudukan Bank Indonesia (BI) sebagai Pemohon Pailit Setelah Berdirinya Otoritas Jasa Keuangan (OJK) - I Komang Mudita Mudita; I Nyoman Sujana; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2020)
In its development banking institutions play a very important role and Act Number 3 of 2004 concerning About Bank Indonesia. After the birth of Law Number 21 of 2011 concerning the Financial Services Authority. It is very interesting to study. What are the considerations taken by Bank Indonesia as a Bankrupt Petitioner after the existence of the Financial Services Authority and What is the Role of Bank Indonesia in Resolving Bankrupt Requests Against Banks. In this study the author uses the type of normative research from primary legal sources secondary legal materials. Article 2 paragraph (3) No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations gives Bank Indonesia sole authority to submit bankruptcy applications to banks as creditors. the results of this study indicate that the authority to submit bankruptcy bank applications after the establishment of the Financial Services Authority the Financial Services Authority is to take into account whether the banks status has a systemic impact when the bank is filed for bankruptcy statements. The Financial Services Authority in this case can request consideration with Bank Indonesia about systemic impact of a bank. But the fact is Bank Indonesia still has authority of macropudentials